Iguratimod Attenuates Macrophage Polarization and Antibody-Mediated Rejection After Renal Transplant by Regulating KLF4 - Hang, Zhou; Wei, Jintao; Zheng, Ming; Gui, Zeping; Chen, Hao; Sun, Li; Fei, Shuang; Han, Zhijian; Tao, Jun; Wang, Zijie; Tan, Ruoyun; Gu, Min (Frontiers in Pharmacology, 2022)
Background: This study aimed to explore the effect and mechanism of iguratimod (IGT) on M1 macrophage polarization and antibody-mediated rejection (ABMR) after renal transplant. Methods: Bioinformatics analysis was performed using three public databases derived from the GEO database. Sprague–Dawley (SD) rats were pre-sensitized with donors of Wistar rats in skin transplantation and a rat renal transplant ABMR model was established from the donors to skin pre-sensitized recipients. Subsequently, IGT was treated on the ABMR model. Routine staining and immunofluorescence (IF) staining were performed to observe the pathological changes in each group and flow cytometry was performed to detect the changes of DSA titers in peripheral blood. In addition, bone-marrow-derived macrophage (BMDM) was extracted and interfered with IGT to explore the effect of IGT in vivo. PCR, IF staining, and Western blot were used to detect the expression of related genes and proteins. Results: Bioinformatics analysis revealed that several immune cells were significantly infiltrated in the ABMR allograft, while M1 macrophage was noticed with the most significance. Results of IF staining and PCR proved the findings of the bioinformatics analysis. Based on this, IGT was observed to significantly attenuate the degree of peritubular capillary vasculitis and arteriolitis in the rat renal transplant ABMR model, whereas it decreases the expression of C4d and reduces the titer of DSA. Results in vitro suggested that M1 macrophage-related transcripts and proteins were significantly reduced by the treatment of IGT in a dose- and time-dependent manner. Furthermore, IGT intervention could remarkably decrease the expression of KLF4. Conclusion: Polarization of M1 macrophages may aggravate ABMR after renal transplant by promoting DSA-mediated endothelial cell injury, and IGT may attenuate the pathogenesis of ABMR by targeting KLF4.